Crocin, a natural molecule with potentially beneficial effects against skin ageing. (9th August 2018) - Fagot, D.; Pham, D. M.; Laboureau, J.; Planel, E.; Guerin, L.; Nègre, C.; Donovan, M.; Bernard, B. A.
Abstract: Objective: Oxidative stress and low‐grade chronic inflammation stand out as key features of physiological skin ageing. The aim of this study was to examine in normal human epidermal keratinocytes (NHEK) and human dermal fibroblasts (HDF) grown in vitro, the antioxidant and anti‐inflammatory properties of crocin, a carotenoid glycoside responsible for the colour of saffron. Moreover, considering the newly emerging field of skin glycobiology and the presence of two gentiobiosyl moieties in crocin, the effect of crocin on NHEK glycosylation pathways was for the first time investigated. Methods: The anti‐inflammatory and antioxidant activities of crocin were evaluated by in vitro assays of antioxidation activities, ELISA and microarray analysis. The effect of crocin on keratinocyte glycobiology was evaluated by proprietary GLYcoDiag lectin technologies and microarray analysis. Results: Crocin is endowed with antioxidant potential against reactive oxygen species, protects squalene against UVA‐induced peroxidation and prevents the release of inflammatory mediators. The expression of NF‐kB‐related genes and glycosylation‐related genes is modulated in the presence of crocin. Conclusion: Results could designate this molecule as a promising skin ageing prevention cosmetic agent. Of note, some of these effects could be mediated by protein O‐glycosylation and interaction of crocin with osidic receptors of keratinocytes. Abstract : Crocin is a carotenoid‐( β ‐D‐gentiobiosyl) di‐ester responsible for the color of saffron. It is endowed with antioxidant potential against ROS, protects squalene against UVA‐induced peroxidation and prevents the release of inflammatory mediators. In human keratinocytes, the expression of NF‐kB related genes and glycosylation related genes is modulated in the presence of crocin. Of note, some of these effects could be mediated by protein O‐glycosylation and interaction of crocin with osidic receptors of keratinocytes.